The Quality Assurance of Strategic Management Consulting Firms - Schmuck, Roland (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2020)
Defining quality in most institutions are clear and easy to do. However quality management is hard to define in case of services because services do not have such generally common, measureable and comparable features like products. In case of services without exact outcomes are even harder to define quality. Strategic management consulting is such a service. Strategic consultants help organizations so solve complex, messy problems. It is very hard to define quality in this case. There is no one best way to manage quality in this case. The goal of this paper is to clarify how quality management can work in such circumstances in the strategic management consulting services industry. The paper is based on literature research and the author’s own experiences as a certified ISO 9001 auditor. This gives a quality standard view of the paper, however other aspects are discussed as well. Strategic management consulting firms have to build trust. This is an important reason to concentrate on quality. Consulting companies can use several methods to increase their service quality. Mostly soft methods can be used because of the limited availability of possible statistical data. The most typical soft methods are shown in this paper. Many of the consulting firms operate ISO 9001 standard-based quality management systems or TQM in their own organizations. Back in time this was a different story. In the 1980s consulting firms rather worked on their clients’ quality concerns not on their own. This has change a lot since that. Nowadays there is a high need of quality operation with reduced costs that the consulting firms themselves also operate quality management systems. These systems can reduce their costs as well by making better decisions and decreasing the cost of bad quality such as faulty fulfillment and guarantee costs. The features of the ISO 9001 standard are shown in this paper regarding the management consulting sector. Quality is becoming a major issue for consulting companies to get new contracts. This is an industry based mainly on trust because the outcome of the service is not immediate and can hardly be measured. Consulting companies should not only keep the technical standards but have to satisfy the customers’ requirements to provide a quality service.